Nourishing island food systems in Solomon Islands: Operational Plan 2024 - Eriksson, Hampus; Aropa, Aloysius; Batalofo, Margaret; Bennet, Gregory; Harohau, Daykin; Hunnam, Kimberly; Leinga, George; Orirana, Grace; Pua'ara, S; Siota, Faye Aborina; Sukulu, Meshach; Wate, Jillian Tutuo; et al. (WorldFish, 2024)
The 2023 Operational plan outlined 27 milestones that we sought to complete during the year. Here we provide a brief traffic light review of milestone completion organised by each of the four research pathways in our 2023 Operational plan. The fifth research pathway, the Nusatupe innovation hub, is an addition to the 2024 plan and is not reported on here. We also map our milestones to three impact pathways to scale research: Targeted capacity development (C), Science based innovation (I), and Advice on policy (P). These impact pathways are described in more detail later in the Operational plan but indicated here to gauge effort in these thematic areas.